Current Vol. 7 No. 1 - Alma Gonzalez:::Editor:::; Robin Excott:::Editor::: (Office of University Advancement, California State University Channel Islands)
President's Message: As I begin my second year as President of Cal State Channel Islands, I look back on all that we have accomplished in 12 short months with a genuine sense of satisfaction and appreciation. Satisfaction because we have accomplished all that we set out to do on June 18, 2001, the day I arrived officially on campus.